Low-Density Lipoprotein Internalization, Degradation and Receptor Recycling Along Membrane Contact Sites - Islam, Mohammad Majharul; Hlushchenko, Iryna; Pfisterer, Simon G. (Frontiers in Cell and Developmental Biology, 2022)
Low-density lipoprotein (LDL) internalization, degradation, and receptor recycling is a fundamental process underlying hypercholesterolemia, a high blood cholesterol concentration, affecting more than 40% of the western population. Membrane contact sites influence endosomal dynamics, plasma membrane lipid composition, and cellular cholesterol distribution. However, if we focus on LDL-related trafficking events we mostly discuss them in an isolated fashion, without cellular context. It is our goal to change this perspective and to highlight that all steps from LDL internalization to receptor recycling are likely associated with dynamic membrane contact sites in which endosomes engage with the endoplasmic reticulum and other organelles.